2009
DOI: 10.1007/bf03346548
|View full text |Cite
|
Sign up to set email alerts
|

Impaired hypothalamo-pituitary-adrenal axis in patients with ankylosing spondylitis

Abstract: Our results indicate an increased prevalence of subclinical glucocorticoid deficiency in AS patients. Anti-TNF treatment seems not to have effect on HPA axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…52 A study examining the low-dose adrenocorticotropic hormone (ACTH) test (LDST) showed that after low-dose ACTH, the cortisol increment was significantly lower in AS patients than in controls (20.0 ± 4.4 vs 24 ± 2.2 microg/dl, P < 0.001). 53 The subclinical glucocorticoid deficiency indicated an impaired hypothalamic-pituitary-adrenal (HPA) axis in AS patients, suggesting the involvement of the endocrine system in the etiology of AS.…”
Section: Introductionmentioning
confidence: 99%
“…52 A study examining the low-dose adrenocorticotropic hormone (ACTH) test (LDST) showed that after low-dose ACTH, the cortisol increment was significantly lower in AS patients than in controls (20.0 ± 4.4 vs 24 ± 2.2 microg/dl, P < 0.001). 53 The subclinical glucocorticoid deficiency indicated an impaired hypothalamic-pituitary-adrenal (HPA) axis in AS patients, suggesting the involvement of the endocrine system in the etiology of AS.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, both regimens could not reduce IR and glucose metabolism. Evidence has shown that there was no effect of OCP containing cyproterone acetate on IR and glucose metabolism after 3 months of treatment . With a longer duration of using OCP, there have been contradictory data on the impact of OCP on IR .…”
Section: Discussionmentioning
confidence: 99%
“…Low serum levels of sex hormones, especially dehydroepiandrosterone sulfate (DHEAS) (i.e., androgen drain), may also contribute to bone loss in patients with AS, while patients with early or adult reactive arthritis have a high cortisol and DHEA serum levels that might change the course of disease (40,41). After administration of a low-dose of adrenocorticotropic hormone (ACTH), the serum cortisol rise became significantly lower in patients with AS than in controls, suggesting an impaired hypothalamic-pituitary-adrenal (HPA) axis and reinforcing the possibility of involvement of the neuroendocrine system in the etiology of AS ("the disproportion principle") (42). More importantly, low cortisol and testosterone serum levels were found in subjects with active JIA, while the lowest androgen levels were found in those patients in whom disease extended into their adult life (43).…”
Section: Stressors Exposure and Neuroendocrine Immuno-modulationmentioning
confidence: 99%